Chimney Technique in Supra-Aortic Branch Reconstruction in China: A Systematic and Critical Review of Chinese Published Experience. (August 2017) - Zhao, Yang; Shi, Yawei; Wang, Mian; Cui, Jin; Chen, Yitian; Zheng, Liang; Yin, Henghui; Chang, Guangqi
Background: The chimney graft (CG) technique has been proposed as a complete endovascular supra-aortic branch reconstruction for aortic pathologies. Due to the rapid growth of thoracic endovascular aortic repair (TEVAR) in China, we aimed to investigate the current data of the CG technique in this most populous country. Methods: Studies of supra-aortic branch reconstruction using the CG technique from Chinese centers were collected and analyzed. Results: A total of 294 patients from Chinese centers who underwent TEVAR with CGs were included. There were 301 CGs performed, with a technical successful rate of 97.7%. The rate of early type I endoleaks was 7.1%, and the patency rate of the CGs was desirable. Balloon-expandable bare CGs were significantly associated with good early outcomes and a low rate of endoleaks. Conclusion: Current data from China revealed positive outcomes using CGs for supra-aortic branch reconstruction. Balloon-expandable bare CGs may be the first choice according to the data available but should be considered with caution.